Effect of some environmental factors on liana abundance in a regenerating secondary lowland rainforest in Nigeria three decades after a ground fire - Uwalaka, Nelson O.; Khapugin, Anatoliy A.; Muoghalu, Joseph I. (Ecological Questions, 2020)
This study examined variation in liana composition, abundance and environmental variables associated with them in a regenerating secondary rainforest in Ile-Ife, Nigeria. Six sample plots were established in the secondary forest in locations undergoing different degrees of regeneration for this study. All individual lianas were enumerated and girths at breast height were measured. Five soil samples were randomly collected from each sample plot using a soil auger, air-dried and sieved, and were analyzed for pH, particle size distribution, organic carbon, total nitrogen, phosphorus, exchangeable cations and organic matter content. Using Canonical Correspondence Analysis, Correlation and regression analysis, we determined soil variables that influenced the liana abundance in the forest. There were 41 liana species in the forest with Motandra guineensis (Apocynaceae) being the most important species. The soil variables affected the liana species differently with the “group IV” liana species showing more preference for all the environmental variables. Liana individuals showed no significant relationship with all the soil variables in the forest. Also, only Motandra guineensis showed a strong relationship with all the soil variables in the forest. The study concluded that soil variables affected the liana abundance in the forest differently.